2022
DOI: 10.3390/biology11020224
|View full text |Cite|
|
Sign up to set email alerts
|

Platelet–Leucocyte Aggregates as Novel Biomarkers in Cardiovascular Diseases

Abstract: Platelet–leucocyte aggregates (PLA) are a formation of leucocytes and platelets bound by specific receptors. They arise in the condition of sheer stress, thrombosis, immune reaction, vessel injury, and the activation of leukocytes or platelets. PLA participate in cardiovascular diseases (CVD). Increased levels of PLA were revealed in acute and chronic coronary syndromes, carotid stenosis cardiovascular risk factors. Due to accessible, available, replicable, quick, and low-cost quantifying using flow cytometry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 183 publications
(337 reference statements)
0
14
0
Order By: Relevance
“…According to experimental evidence, the “regulation of angiogenesis” is involved in plaque formation [ 89 ] and may cause many diseases such as cardiovascular disease and diabetic microvascular complications [ 90 ]. Research consistently showed that regardless of disease severity, “leukocyte aggregation” is an independent indicator of future cardiovascular outcomes, and it has been investigated extensively as a biomarker in cardiovascular diseases [ 91 , 92 ]. Chemokines are small chemotactic cytokines that trigger integrin activation to induce firm arrest of leukocytes on activated endothelium, thus “positive regulation of chemokine production” contributing to the development of atherosclerosis [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to experimental evidence, the “regulation of angiogenesis” is involved in plaque formation [ 89 ] and may cause many diseases such as cardiovascular disease and diabetic microvascular complications [ 90 ]. Research consistently showed that regardless of disease severity, “leukocyte aggregation” is an independent indicator of future cardiovascular outcomes, and it has been investigated extensively as a biomarker in cardiovascular diseases [ 91 , 92 ]. Chemokines are small chemotactic cytokines that trigger integrin activation to induce firm arrest of leukocytes on activated endothelium, thus “positive regulation of chemokine production” contributing to the development of atherosclerosis [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…The binding of P-selectin on platelets to leukocyte (mostly monocyte) surface PSGL-1 (P-selectin glycoprotein ligand) is an important event that enhances monocyte activation. In addition, this binding increases αMβ2 integrin (Mac-1, CD11b/CD18) expression, which stabilizes the complex and is crucial for the survival of circulating MPAs [ 23 , 27 ]. Our previous study observed an obvious increase of CD11b expression in MPA-mediated monocytes [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The formation of platelet-leukocyte aggregates mediates outside-in signaling events and, thus, facilitates leukocyte migration and function [ 10 ]. Leukocytes may bind a varying number of platelets and complexes may appear either unbound in the circulation or bound to vessel walls and tissues [ 85 ]. Flow cytometry, tissue section imaging and live cell imaging represent the most common tools to analyze platelet leukocyte aggregates by applying specific fluorescent antibodies to identify different cell populations [ 86 ].…”
Section: Immune-modulatory Function Of Plateletsmentioning
confidence: 99%
“…A growing body of literature has examined platelet–leukocyte interactions under disease conditions, indicating their prominent role for a comprehensive immune response. In addition, platelet–leukocyte aggregates have been suggested as potential biomarkers in various pathologies including pulmonary diseases, vasculitis and cardiovascular diseases [ 85 ].…”
Section: Immune-modulatory Function Of Plateletsmentioning
confidence: 99%